Aktivitas Senyawa Isolasi Daun Surian terhadap Disfungsi Sel Endotel Hiperkholesterolemia - Suhatri, .; Yanwirasti, .; Dachriyanus, .; Ellyza, . (JFIOnline | Print ISSN 1412-1107 | e-ISSN 2355-696X)
The protective effects of isolated compounds of ethylacetate fraction of surian's leaf (Toona sureni BL Merr) towards endothelial cell dysfunction on hypercholesterolemia have been investigated. Hypercholesterolemia was induced by atherogenic cocktail for the duration of 60 days. The protective effect was determined by Endothelia Derivate Relaxing Factor 9EDRF/NO) concentration. The result showed that isolated compounds oe ethyl acetate fraction of surian's leaf was able to protect the endothelia cell damage in hypercholesterolemia that can be seenn by increasing the bioavailability of NO serum (P<0.05).Keywords : flavonoid, cocktail, hypercholesterol and nitrogen mono oxide (EDRF)